International Trade Outlook for Latin America and the Caribbean 2017 - Economic Commission for Latin America; the Caribbean (United Nations, 2017)
This first edition of International Trade Outlook for Latin America and the Caribbean, which is the continuation of Latin America and the Caribbean in the World Economy with a new title, covers 2017 and contains three chapters. The first chapter describes the current international context and the recovery of trade in the region. Chapter II reviews the region’s performance in global trade in services in general and in modern services in particular, since 2005. Chapter III provides an overview of Latin America and the Caribbean’s share of the world agricultural trade since 2000 and offers some policy recommendations for increasing the sector’s contribution to regional development.